THE SOCIAL PEDAGOGICAL NECESSITY OF DEVELOPING STUDENTS’ AESTHETIC CULTURE IN THE PROCESS OF GLOBALIZATION - SIDDIKOV BAKHTIYOR SAIDKULOVICH; TADJIBAYEV JAHONGIR UMIDJON UGLI (International Journal of Innovations in Engineering Research and Technology, 2021)
In this article given information and discuss the content and essence of the concepts of “aesthetics”, “aesthetic culture”, as well as the social and pedagogical necessity of developing the aesthetic culture of students in the process of globalization.